Systemic lupus erythematosus in male: two case reports - Hossain, Md Ismail; Jahan, Shah Md Sarwer; Haque, Md Ashraful; Alam, ABM Mobasher; Ahmed, Mainuddin; Hossain, Md Zakir (Bangladesh Journal of Medicine, 2014)
Systemic lupus erythematosus (SLE) is the most common multisystem connective tissue disease. Around 90% of affected individuals are women, with peak onset in the second and third decades. Tissues of all system are damaged by pathogenic auto-antibodies and immune complexes. We report here two cases of SLE in male patient, presented with typical features of SLE. Though the disease is rare in male, but such type of manifestations should be investigated properly to exclude SLE. DOI: http://dx.doi.org/10.3329/bjmed.v24i2.20222 Bangladesh J Medicine 2013; 24 : 82-85